Numerical Validation of Brenner's Hydrodynamic Model by Force Driven Poiseuille Flow (Advances in Applied Mathematics and Mechanics, 2018)
Recently Brenner [Physica A 349, 60 (2005)] proposed amodified Navier-Stokes set of equations. Based on some theoreticalarguments and some limited experiments, the model is expected to beable to describe flows with a finite Knudsen number. In this work,we apply this model to the plane Poiseuille flow driven by a force,and compare the results with the Direct Simulation Monte Carlo(DSMC) measurements. It is found that Brenner's model is inadequatefor flows with a finite Knudsen number.